2022
DOI: 10.3892/mmr.2022.12915
|View full text |Cite
|
Sign up to set email alerts
|

ANRIL overexpression globally induces expression and alternative splicing of genes involved in inflammation in HUVECs

Abstract: long non-coding (lnc)rnas serve important cellular functions and certain lncrnas have roles in different mechanisms of gene regulation. lncrna-antisense non-coding rna in the INK4 locus (ANRIL) affects cell inflammation; however, the potential genes underlying the inflammatory response regulated by anril remain unclear. in the present study, the potential function of anril in regulating gene expression and alternative splicing was assessed. ANRIL-regulated human umbilical vein endothelial cell (HUVEC) transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…[30][31][32][33] The study revealed that ANRIL exerted an influence on the transcription levels of genes associated with the inflammatory response, NF-κB signaling pathway, type I interferon-mediated signal transduction pathway, and innate immune response in HUVEC. 34 Consistent with the literature, this research found that LPS caused increases in IL-1β, IL-6, and TNF-α expressions, and si-ANRIL could alleviate this phenomenon, which meant the alleviation of inflammation. Moreover, the knockdown of lnc-ANRIL released the oxidative stress induced by LPS.…”
Section: Discussionsupporting
confidence: 88%
“…[30][31][32][33] The study revealed that ANRIL exerted an influence on the transcription levels of genes associated with the inflammatory response, NF-κB signaling pathway, type I interferon-mediated signal transduction pathway, and innate immune response in HUVEC. 34 Consistent with the literature, this research found that LPS caused increases in IL-1β, IL-6, and TNF-α expressions, and si-ANRIL could alleviate this phenomenon, which meant the alleviation of inflammation. Moreover, the knockdown of lnc-ANRIL released the oxidative stress induced by LPS.…”
Section: Discussionsupporting
confidence: 88%
“…ANRIL overexpression is associated with in ammatory response in IS [29], The possible mechanism involved in pro-in ammatory effect of ANRIL include; increase in NF-κB expression [30], type I interferon-mediated signal transduction pathway and innate immune response [31]. On the other hand, the ANRIL downregulation with anti-in ammatory effects has been suggested in in ammatory bowel disease (IBD) [32], attenuating the atherosclerosis progression in CAD patients[8] ,and acute ischemic stroke [33].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ANRIL negatively and positively influences gene expression at the chromatin level [247]. ANRIL functions as a scaffold for PRC2 and, therefore, participates in epigenetic gene silencing [250] and is involved in alternative splicing in HEK293 and HUVEC cells [251]. Through these mechanisms, ANRIL contributes to tumourigenesis processes, increasing cell proliferation, migration, invasion, and metastasis and suppressing apoptosis and senescence [248].…”
Section: Emerging Lncrna Biomarkers Of Gbmmentioning
confidence: 99%